2011
DOI: 10.1080/09687599.2011.544060
|View full text |Cite
|
Sign up to set email alerts
|

‘I want support, not comments’: children's perspectives on supports in their life

Abstract: Supports are a major part of the daily lives of children with special educational needs who participate in general education schools. Little attention has been paid to how they experience supports. Six children and their peers who were interviewed appreciated supports because they remove restrictions in activities due to the impairment.However, the analysis also shows how these positive supports can have negative psycho-emotional repercussions, and that they are less focused on addressing disabling barriers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
(29 reference statements)
1
42
0
Order By: Relevance
“…Giangreco (2009, p. 3) cautions that 'the nature of the support [provided to students with disabilities] may be inconsistent with individual goals that are geared toward greater student independence' , which was evident in this case, to the detriment of the young people's inclusion. These findings are consistent with other studies (Broer et al, 2005;De Schauwer et al, 2009;Mortier et al, 2011;Tews & Lupart, 2008), and show that young people with VI feel similarly towards paraprofessionals, as do those with intellectual and other impairments.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Giangreco (2009, p. 3) cautions that 'the nature of the support [provided to students with disabilities] may be inconsistent with individual goals that are geared toward greater student independence' , which was evident in this case, to the detriment of the young people's inclusion. These findings are consistent with other studies (Broer et al, 2005;De Schauwer et al, 2009;Mortier et al, 2011;Tews & Lupart, 2008), and show that young people with VI feel similarly towards paraprofessionals, as do those with intellectual and other impairments.…”
Section: Discussionsupporting
confidence: 95%
“…Students in receipt of paraprofessional support appear to constantly experience feelings of dependence on support personnel, which negatively affected their sense of autonomy (Tews & Lupart, 2008). Furthermore, the studies reported that students often felt controlled by support personnel (Broer et al, 2005;De Schauwer et al, 2009;Mortier et al, 2011;Tews & Lupart, 2008). Students who attended classes accompanied by paraprofessionals continually compared themselves against their peers who did not receive support.…”
Section: Students' Views Of Paraprofessional Supportmentioning
confidence: 93%
See 1 more Smart Citation
“…This disparity could suggest different priorities for the two groups, with pupils feeling that they need help with academic tasks and TAs more focused on managing pupil behaviour. This is an interesting finding, given research that has suggested pupils do not always feel able to have autonomy over how they are supported and may be supported with tasks where they feel they do not need help (Mortier et al ., ; Tews and Lupart, ).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…There has been little research in relation to pupil perspectives of TAs and their understanding of the TA role. Where researchers have spoken to pupils, the children interviewed have most often spoken positively about TAs' support, saying that they enjoy the company of their TA and appreciate the support for things they find challenging within school (Mortier et al, ). In other studies, however, pupils have also expressed concerns about the support received from TAs, including a feeling that pupils lacked autonomy and control over how they were helped in school (Skar and Tamm, ; Tews and Lupart, ).…”
Section: Introductionmentioning
confidence: 99%